Enhanced electrochemical charge storage performance by doping of copper phthalocyanine-3, 4′, 4″, 4‴-tetrasulfonic acid tetrasodium salt into polypyrrole/multi-walled carbon nanotubes 3D-nanostructured electrodes. (1st March 2018) - Lu, Yuanchao; Zheng, Qiqi; Wu, Jian; Yu, Yonghua
Abstract: With the increasing focus on energy crisis and environmental protection, polypyrrole/muti walls carbon nanotubes (PPy/MWCNTs) composites which possess relatively high specific capacitance are a class of promising electrode active material for energy storage devices. This study proposes a method using two dopants, copper phthalocyanine-3, 4′, 4″, 4‴-tetrasulfonic acid tetrasodium salt (CuPcTs) and phytic acid (PA), for adjusting the porous nanostructure and improving the electrochemical performance of PPy/MWCNTs electrodes. Compared with the particle-like PPy/MWCNTs and PA-PPY/MWCNTs (p-PPy/MWCNTs) electrodes, the 3D fiber-like CuPcTs-PPy/MWCNTs (c-PPy/MWCNTs) electrodes with a smaller diameter and higher specific surface area can provide more electron successive pathways and ion diffusion tunnels and active sites. The c-PPy/MWCNTs electrodes exhibit the highest specific capacitance of 488 F g −1 @ 5 A g −1 and 451 F g −1 @ 10 mV s −1, which is approximately 2 and 1.6 times of p-PPy/MWCNTs and PPy/MWNCTs with the specific capacitance of 265 F g −1 @ 5 A g −1 and 246 F g −1 @ 5 A g −1 and 288 F g −1 @ 10 mV s −1 and 267 F g −1 @ 10 mV s −1, respectively. The PPy/MWCNTs doping with CuPcTs can be used as an excellent electrode for the fabrication of energy storage devices and affords a modifying method for other active materials.